Effect of sub-inhibitory concentrations of antibiotic on the production and N-acetylglucosamine scale of methicillin- resistant Staphylococcus aureus biofilm - Moori Bakhtiari, N; Ezzati Givi, M; Goudarzi, S (Journal of the Hellenic Veterinary Medical Society, 2023)
The ability of Staphylococcus spp. to produce biofilm is one of the virulence factors that facilitate the adhesion and colonization on a different surface. In this study, the effects of sub minimum inhibitory concentration (sub-MIC) of some antibiotics were evaluated on induction of the biofilm producing ability and free N-acetylglucoseamine scale in 29 isolates of methicillin resistance staphylococcus aureus. To this end, the antibiogram and biofilm producing functions of the studied isolates were assessed by Kirby-Bauer and tissue culture plate method, respectively. Vancomycin, trimethoprim-sulfamethoxazole and clindamycin were used in antibiogram. The free N-acetylglucoseamine scale in the inducted biofilm after treatment with antibiotic was evaluated by TLC method. Based on the attained results, all the isolates were susceptible to vancomycin and were capable of producing biofilm in weak (40%), moderate (56.6%) and strong (3.33%) levels. Also, biofilm production was induced in 36.66% of isolates (11/30) from moderate to strong level by sub-MIC vancomycin. An invisible change in free N-acetyl glucoseamine scale was demonstrated in the exopolysaccharide (EPS) structure of the studied isolates biofilm. By comparing of results and literature reviews, free N-acetyl glucoseamine scale in all studied strains was lower than 5µg in before and after inducted biofilm or maybe is not exist. Certainly, for studied of structural N-acetyl glucoseamine scale, using more exact methods of extraction and measurement are need.